Determinant tax aggressiveness in Indonesia: The Influence of Profitability, Leverage, and Liquidity - Sandi Nasrudin Wibowo; Nelia Fariani Siregar; Rendi Febriansyah (RTTM, 2023)
Tax is one of the important elements that contribute to community service. The purpose of this research is to determine the relationship between tax aggression (TA) and the factors of Profitability (PRFT), Leverage (LVG), and Liquidity (LIQ). This study used secondary data from the company's annual report accessed through the company's official www.idx.co.id website. The research population consisted of the 48 mining businesses listed on the Indonesia Stock Exchange (IDX) during the years 2017 and 2021. Purposive sampling used a sample of 70 company data to select the sample in this study. The data analysis method involved in this study was multiple regression analysis. The data were analyzed using version 25 of the SPSS software for Windows. The results of this study show that PRFT and LIQ affect TA, while LVG does not affect TA. This research can contribute to the government, especially in increasing taxpayer compliance through factors that influence TA